Functional Genomic Analyses Identify Pathways Dysregulated in Animal Model of Autism. (20th June 2016) - Huang, Ji‐Yun; Tian, Yun; Wang, Hui‐Juan; Shen, Hong; Wang, Huan; Long, Sen; Liao, Mei‐Hua; Liu, Zhi‐Rong; Wang, Ze‐Ming; Li, Dan; Tao, Rong‐Rong; Cui, Tian‐Tian; et al.
Summary: Background: Autism spectrum disorders (ASDs) are a heterogeneous group of neurodevelopmental disorders that display complicated behavioral symptoms. Methods: Using gene expressing profiling and the weighted gene co‐expression network analysis (WGCNA), we studied genes coregulated by similar factors such as genetic variants or environmental effects in the hippocampus in an animal model of autism. Results: From microarray data, we identified 21, 388 robustly expressed genes of which 721 genes were found to be differently expressed in the valproic acid‐treated group compared to the control group. WGCNA identified multiple co‐expression modules known to associate with cognitive function, inflammation, synaptic, and positive regulation of protein kinase activating. Many of these modules, however, have not been previously linked to autism spectrum disorders which included G‐protein signaling, immunity, and neuroactive ligand–receptor interaction pathway. The downregulation of the highly connected (hub) genes Taar7h and Taar7b in neuroactive ligand–receptor interaction pathway was validated by qRT‐PCR. Immunoblotting and immunohistochemistry further showed that TAAR7 expression was downregulated not only in valproic acid‐treated animals, but also BTBR T+tf/J mice. Conclusions: This study highlights the advantages of gene microarrays to uncover co‐expression modules associated with autism and suggests that Taars and related gene regulation networks may play a significant role in autism.